Cobalt protoporphyrin IX increases endogenous G‐CSF and mobilizes HSC and granulocytes to the blood - Szade, Agata (EMBO Mol Med, 2019)
Granulocyte colony‐stimulating factor (G‐CSF) is used in clinical practice to mobilize cells from the bone marrow to the blood; however, it is not always effective. We show that cobalt protoporphyrin IX (CoPP) increases plasma concentrations of G‐CSF, IL‐6, and MCP‐1 in mice, triggering the mobilization of granulocytes and hematopoietic stem and progenitor cells (HSPC). Compared with recombinant G‐CSF, CoPP mobilizes higher number of HSPC and mature granulocytes. In contrast to G‐CSF, CoPP does not increase the number of circulating T cells. Transplantation of CoPP‐mobilized peripheral blood mononuclear cells (PBMC) results in higher chimerism and faster hematopoietic reconstitution than transplantation of PBMC mobilized by G‐CSF. Although CoPP is used to activate Nrf2/HO‐1 axis, the observed effects are Nrf2/HO‐1 independent. Concluding, CoPP increases expression of mobilization‐related cytokines and has superior mobilizing efficiency compared with recombinant G‐CSF. This observation could lead to the development of new strategies for the treatment of neutropenia and HSPC transplantation.